PENGARUH LIKUIDITAS, LEVERAGE, DAN PROFITABILITAS TERHADAP KINERJA PERUSAHAAN (STUDI PADA PERUSAHAAN SUB-SEKTOR MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA TAHUN 2018 – 2020) - Titin Tri Ego; Ibnu Hajar; Dedy T akdir S; Wahyuniati Hamid; Zaludin Zaludin (Jurnal Manajemen dan Kewirausahaan, 2022)
The purpose of this study is to explain the Effect of Liquidity, Leverage, and Profitability on Company Performance in Companies Listed on the Indonesia Stock Exchange 2018 - 2020. The objects in this study are Companies Listed on the Indonesia Stock Exchange, totaling 13 samples from the population and having financial statement data. By using the panel data regression analysis method. The sampling technique in this study used the purposive sampling technique.  The results of this study indicate that the Current Ratio has a significant negative effect on the company's performance, the Debt to Equity Ratio (DER) has a significant positive effect on the company's performance, and the Net Profit Margin (NPM) has a significant positive effect on the company's performance.